2023
DOI: 10.3389/fmolb.2023.1156062
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of cervical cancer to dihydroartemisinin-induced ferritinophagy-dependent ferroptosis

Abstract: The clinical therapeutics of cervical cancer is limited due to the drug resistance and metastasis of tumor. As a novel target for antitumor therapy, ferroptosis is deemed to be more susceptible for those cancer cells with resistance to apoptosis and chemotherapy. Dihydroartemisinin (DHA), the primary active metabolites of artemisinin and its derivatives, has exhibited a variety of anticancer properties with low toxicity. However, the role of DHA and ferroptosis in cervical cancer remained unclear. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Our results also identified that the cases of HPV infection genotype and frequency were significantly lower in people under 30 than in other age groups, which is supported by the study of Fatima Mijit et al ( 27 ). This suggests that the lower positivity rate of HPV in women under 30 may be due to their higher immune levels ( 28 , 29 ). However, cases of advanced cervical cancer have also been reported in women under 30 years old in recent years ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also identified that the cases of HPV infection genotype and frequency were significantly lower in people under 30 than in other age groups, which is supported by the study of Fatima Mijit et al ( 27 ). This suggests that the lower positivity rate of HPV in women under 30 may be due to their higher immune levels ( 28 , 29 ). However, cases of advanced cervical cancer have also been reported in women under 30 years old in recent years ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“… 7 In addition, microRNA-660-5p has been shown to inhibit ferroptosis in SiHa cells, 23 while DHA can trigger ferritinophagy-dependent ferroptosis in SiHa cells. 24 Ferrostatin-1 is a specific ferroptosis inhibitor that prevents erastin-induced lipid ROS accumulation and inhibits ferroptosis in fibrosarcoma HT-1080 cells. 4 In the present work, ferrostatin-1 markedly diminished the suppressing activity of erastin on both HeLa and SiHa 24 cell growth, motility, and ROS production.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Ferrostatin-1 is a specific ferroptosis inhibitor that prevents erastin-induced lipid ROS accumulation and inhibits ferroptosis in fibrosarcoma HT-1080 cells. 4 In the present work, ferrostatin-1 markedly diminished the suppressing activity of erastin on both HeLa and SiHa 24 cell growth, motility, and ROS production.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Furthermore, ferroptosis is involved in the occurrence and development of cervical cancer and is related to its prognosis. 26 , 27 , 28 , 29 , 30 Some drugs exert therapeutic effects against cervical cancer through ferroptosis. 31 , 32 , 33 Hypoxia reduces Fenton chemistry and lipoxygenase activity, which are the key control systems for ferroptosis.…”
Section: Introuductionmentioning
confidence: 99%